Productive reconversion as a result of Huanglongbing presence in Colima, México - Hernández Hernández, Raciel; Granados Ramírez, Guadalupe Rebeca; Mora Aguilera, Gustavo; Aguirre Gómez, Raúl; León García, Imelda (Acta Universitaria, 2019)
Colima state is one of the most important leading producers of lemon, and it has been affected by Huanglonbing (HLB); the damage has spread and caused a progressive production loss in the lemon production chain. So far, there is no cure and farmers have decided to make changes in the crops’ dynamic. The objective of the present work was to quantify the changes in the planted area through spatial analysis (PR) and geographic information system (SIG) tools. Supervised classifications of Landsat 7 and Landsat 8 images were carried out. It was proved that lemon crop was substituted progressively by other crops during the last five years. Until now, 5000 ha of citrus have been substituted. This has implied a reduction of 84 721.88 t of Mexican lemon production and a loss of 302 636 729 Mexican pesos.